Escherichia coli O157:H7 Acid Sensitivity Correlates with Flocculation Phenotype during Nutrient Limitation - Kay, Kathryn L.; Breidt, Frederick; Fratamico, Pina M.; Baranzoni, Gian M.; Kim, Gwang-Hee; Grunden, Amy M.; Oh, Deog-Hwan (Frontiers in Microbiology, 2017)
Shiga toxin producing Escherichia coli (STEC) strains vary in acid resistance; however, little is known about the underlying mechanisms that result in strain specific differences. We found that of 25 STEC O157:H7 strains tested, 7 strains flocculated when grown statically for 18 h in minimal salts medium at 37°C while 18 strains did not. Interestingly, the flocculation phenotype (cells came out of suspension) was found to correlate with degree of acid sensitivity when challenged in 400 mM acetic acid solution at pH 3.3. Strains exhibiting flocculation were more acid sensitive and were designated FAS, for flocculation – acid sensitive, while the acid resistant strains were designated PAR, for planktonic – acid resistant. Flocculation was not observed for any strains during growth in complex medium (Luria Bertani broth). STEC strains B201 and B241 were chosen as representative FAS (2.4 log reduction) and PAR (0.15 log reduction) strains, respectively, due to differences in acid resistance and flocculation phenotypes. These strains were used to examine phenotypic differences by electron microscopy and transcriptomics. Results from electron microscopy (for B201 and 241) and a differential medium, used to identify curli fimbriae containing Congo red, showed that production of curli fimbriae present in all FAS strains. Additionally, 5 PAR strains also had evidence of curli production. Transcriptomic and targeted gene expression data for B201 and B241indicated that csg and hde (curli and acid induced chaperone genes, respectively) expression positively correlated with the phenotypic differences observed for these strains. These data suggest that FAS strains grown in minimal medium express curli resulting in a flocculation phenotype, while repressing acid chaperone proteins production, and this may be regulated through GcvB, RpoS and possibly other regulatory mechanisms. These findings may help elucidate mechanisms underlying differences among STEC strains in relating acid resistance and biofilm formation.